PELAKSANAAN RENVOOIPROCEDURE DALAM PERKARA KEPAILITAN DI PENGADILAN NIAGA - Pupung Faisal (Indonesian Journal of Dialectics, 2011)
Renvooiprocedure is one of settlement mechanism on bankruptcy remonstrance. This settlement is limited written on law number 37 years 2004 (UUKPKPU), on article 127 UUKPKPU and article 194 UUKPKPU. This unclear Renvooiprocedure mechanism, result some difficulties among judges and make this procedure has various mechanism. In practice, Renvooiprocedure is used in several civil law procedures as it is stated on article 299 UUKPKPU.This research was using judicial normative method with analitycal descriptive. The data were taken from library research at Mochtar Kusumaatmadja library and field research at Pengadilan Niaga Jakarta Pusat, analyze with qualitative method.It is summarized that the relationship between renvooiprocedure with civil law procedure has shown that this procedure is a part of the whole civil law procedure emphasizing on bankrupty. On its implementation, Renvooiprocedure has been used in  many part on civil law procedure.